The Hybridity of Islam, Hinduism, and Modernity in Troloyo Cemetery - Dian Oktavia; Erlis Hersetya Firda; Happy Julia Rahmadianti; Hariyono Hariyono; Rommel Utungga Pasopati (Jurnal Ilmiah Multidisiplin Amsir, 2026)
Troloyo Cemetery, located in Trowulan, Mojokerto, East Java, is a historical burial site that exemplifies the hybridity between Islam, Hindu-Buddhist traditions, and modernity. This study explores the cemetery as a cultural third space, a concept introduced by Homi K. Bhabha (1994), where different belief systems and historical legacies intersect, negotiate, and form new identities. The research applies a qualitative approach through semi-structured interviews and direct observation, focusing on the perceptions of local caretakers and community members. Findings reveal that Islamic elements are present in tombstone inscriptions, Arabic calligraphy, and pilgrimage practices associated with Syekh Jumadil Kubro, a key figure in Javanese Islamization. Simultaneously, Hindu-Buddhist influences persist through architectural structures like kijing and symbols such as Surya Majapahit, while modern features—such as tourism and infrastructure development—further shape the site's identity. Ritual practices like incense burning, flower offerings, and local cosmological concepts highlight syncretic expressions of spirituality rooted in Javanese culture. These complex layers of religiosity and symbolism challenge rigid categorizations of identity, instead revealing a dynamic cultural landscape formed through historical negotiation and continuity. The study concludes that Troloyo Cemetery functions not merely as a sacred Islamic site but as a hybrid space where cultural and religious forms co-exist and evolve, offering a deeper understanding of Indonesia's plural spiritual heritage.